Prospective outcomes of single incision laparoscopic cholecystectomy compared to conventional laparoscopic cholecystectomy; an initial experience - Samintharapanya, Sahatham (Biomedical Sciences and Clinical Medicine, 2013)
Backgroud Single incision laparoscopic cholecystectomy (SILC) has been challenged as an alternative technique to the gold standard conventional (3 or 4 port) laparoscopic cholecystectomy (LC). Method In a prospective study from March to December 2012, 21 patients with indication of cholecystectomy were randomized into a SILC (n=10) or LC (n=11) group. The primary outcomes were cosmetic result and post operative pain. The secondary outcomes were complications, length of hospital stay (LOS) conversion rate and operative time. Results Patient characteristics were no different between groups, except for body mass index (BMI), which was lower in the SILC group (mean±SD 20.2±2.5 vs 25.4±3.9 kg/m2, p <0.01). The SILC group had a higher cosmetic score (mean±SD 9.7±0.5 vs 7.5±1.1, p <0.01) and longer operative time (mean±SD 84±19.9 vs 55±11.2 min, p<0.01), but was equal in visual analog pain score (VAS) (mean ±SD 3.7±1.6 vs 4.1±1.4, p=0.54), opiate used on day 1 (30% vs 45%, p =0.66), LOS (mean±SD 2.1±0.3 vs 2.2±0.6 day, p =0.70), post operative complication rate (10.0% vs 18.2%, p =1.00) and no conversion rate at all. Conclusion SILC is a safe procedure with better cosmetic results.